PREVALENCE OF MULTI DRUG RESISTANT STRAINS ON TOUCH SCREEN OF AUTOMATED TELLER MACHINE - N, Ramesh; PRAKASH PILLAI, AKSHITA; Nandini RajanNambiar; M, Prasanth; T, Shanthini; Km, Gothandam; S, Karthikeyan (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Multiple drug resistant (MDR) bacteria have spread globally even on non-porous surfaces such as mobile phones, computers, public telephone booths, keypads and touch screens of automatic teller machine (ATM). In this study, occurrence of different groups of MDR bacteria from metallic keypad and touch screens of ATM machine was examined. The samples were collected from different ATMs located in Vellore, Tamil Nadu. Swabs were taken from 47 ATMs and 488 isolates were identified as Escherichia coli (49%), Klebsiella sp., (30%), Pseudomonas sp., (16%), Acinetobacter sp., (3%) and Proteus sp., (1%) and they were subjected to antibiotic susceptibility testing with ampicillin, cefotaxime, ceftriaxone, ceftizidime and meropenem of which 46 isolates showed high level of resistance toward cefotaxime, and meropenem by plate assay. Further polymerase chain reaction amplification of NDM-1 and CTX-M genes for all 46 isolates showed no amplified product, which showed the possibility for the presence of other types of extended spectrum Î²-lactamases or metallo beta-lactamase. Our results showed the prevalence of MDR bacteria in ATM centers and most importantly awareness toward the public regarding the spread of pathogenic bacteria in the environment. Keywords: Multiple drug resistance, Automatic teller machine centers, Public health, Antibiotic susceptibility pattern, Resistance gene.